Concerns of Surgical Assistants - Correspondence: Godkins to Wheeling - Godkins, Thomas R. (1975)
In his 23 July 1975 letter to Glen Wheeling, President of the Association of Surgeon's Assistants, Tom Godkins, AAPA president, notes that the "Academy has within its membership many surgical assistants" and assures Mr. Wheeling that "the Academy will speak much more articulately for surgical assistants in the future." Godkins does not want "fragmentation" caused by development of specialty organizations, "feeling that much more can be accomplished with unity rather than division." The major issue is the development and administration of a surgical examination by the NCCPA. The Academy would prefer all PAs taking a "generic" examination with an add-on surgical examination. He notes that an ad hoc committee had been formed to study certification of the surgical assistant with Craig Ilk as chairman and various surgical assistants as committee members. At some point, Godkins would "like to see the AASA and AAPA merge."